Filtration and prediction of random solutions of a system of linear differential equations with coefficients depending on a finite-valued Markov process - Lapshin, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We obtain an equation of optimal filtration for processes of Markov random evolution, which is a solution of systems of linear differential equations with Markov switchings.